Intrapersonal Communication: Improving Self Awareness Perspective of Al-Qur'an Surah Adz Dzariyat Verses 20 and 21 - Nurrohmah, Shinta; Syayekti, Ela Indah Dwi; Afifah, Nisa (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2024)
Communication plays a role important as a tool to communicate well with the environment in order to establish a harmonious relationship , but it can also become a means of knowing oneself, one of which is in increasing self- awareness for every individual . The purpose of writing this article is to find out the impact of intrapersonal communication on increasing one's self awareness to change perspectives and attitudes for the better according to the perspective of Al-Qur'an Surah Adz Dzariyat verses 20 and 21. Therefore the research library method in this study is used to examine the concept of intrapersonal communication from the perspective of Surah Adz Dzariyat verses 20 and 21 from research books and journals. The results of the discussion of this article are that intrapersonal communication has an impact on each individual to know himself. The significance of the role of intrapersonal communication for individuals towards self-awareness encourages them to do self-introspection and manage the emotions that are being felt so that they can relieve stress and will make individuals focus on life goals . The tendency of awareness to make creative and innovative decisions in dealing with events in life without reducing existing knowledge and directing individuals to positive emotions.